SENIOR HIGH SCHOOL STUDENTS’ READINESS IN USING TECHNOLOGY TO ENHANCE LANGUAGE LEARNING - Virgin Erdia Sandi Putripertiwi; Farouk Imam Arrasyid (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractThis research aimed to investigate students’ readiness in using technology in the learning process, especially for English learning. 21st century has brought the development of various areas, especially for Information and Communication Technology (ICT). ICT is beneficial for various fields including education. Educational technology is the study and ethical practice of encouraging education by designing, using, and managing appropriate technological processes and improving performance. The use of technology has become the perfect complement to master or gain control of a language and English courses are supported by the most efficient and attractive technology in the learning process. This research used qualitative method conducted in Senior High School to explore the views of participants in using technology into language learning activities known as Technology Enhance Language Learning (TELL). Based on the data analysis, the highest result of students’ readiness in using technology shows that there are 19 of 20 students who have capability to use technology to finish English assignments.Keywords: : TELL, learning English, students’ readiness, senior high school